Body-affective dimensions for the school context: theatrical play for social transformation - Melo, Iris Mariano de; Tanzi Neto, Adolfo (The ESPecialist, 2025)
This article explores the corporeal-affective dimensions in the school context, focusing on theatrical practices as tools for social transformation. Based on the approach of authors such as Espinosa (1656/2009), Vygotsky (1978), Spolin (1963) and Boal (2019), this study investigates how body and mind act in an integrated way when mobilized in pedagogical theatrical activities that can play a crucial role in the social development of individuals. Through theatrical games with 6th year students, the study analyzed how these practices encourage the active participation of students, promoting positive and collaborative social encounters that can increase their ability to act and transform their realities. Methodologically, with the contribution of Critical Collaboration Research (PCCol) (Magalhães and Fidalgo, 2019), we developed, critically and collaboratively, pedagogical interventions that could explore everyday social problems of those involved through role-plays. Students, when interacting physically and emotionally, were challenged to find creative solutions to different conflicts. The results indicate that theatrical games contributed to attention, memory and problem-solving potential. At the end of the activities, students demonstrated a greater understanding of the role of emotions and the ability to act critically and collaboratively on their social issues. We conclude that corporeal-affective practices, especially theatrical activities, have significant potential to promote social transformations in the school environment, by integrating body, mind and emotions in the teaching-learning process.